The administration of Enterococcus faecium SF68 counteracts compositional shifts in the gut microbiota of diet-induced obese mice - Panattoni, Adelaide; Calvigioni, Marco; Benvenuti, Laura; D’Antongiovanni, Vanessa; Pellegrini, Carolina; Di Salvo, Clelia; Mazzantini, Diletta; Celandroni, Francesco; Fornai, Matteo; Antonioli, Luca; Ghelardi, Emilia (Frontiers in Microbiology, 2022)
Microorganisms with probiotic properties are eliciting an increasing interest as coadjuvants in the prevention and treatment of obesity through modulation of the gut microbiota. In this study, a probiotic formulation based on Enterococcus faecium SF68 was administered to mice fed with a high-fat diet (HFD) to evaluate its efficacy in reducing body mass gain and in modulating the intestinal bacterial composition. Both stool and ileum samples were collected from untreated and treated mice and absolute abundances of specific taxa constituting the gut microbial consortium were evaluated. SF68 administration significantly reduced the HFD-induced weight gain. In these animals, the microbial gut composition shifted towards an enrichment in microbes positively correlated with mucus thickness, lower inflammation, lower glycemia levels, and SCFA production (i.e., Bifidobacterium, Akkermansia, Faecalibacterium), as well as a depletion in bacterial phyla having a key role in obesity (i.e., Firmicutes, Proteobacteria). Our results demonstrate the efficacy of E. faecium SF68 in adjusting the composition of the dysbiotic microbiota of HFD-fed animals, thus ameliorating clinical conditions and exerting anti-obesity effects.